Odpowiedzi

2010-03-21T13:34:55+01:00
A)5x/2-2(2x+5)=2x-1/2
10x-4x+10=2x-1
10x-4x-2x=-1+10
4x=-9/(-4)
x=2¼

b)x-1/3+5+3=2-x/3
3(x-1)+5+3=2-x
3x-3+5+3=2-x
3x-11=2-x
3x+x=-11-2
4x=-13/4
x=-3½

c)2(2x+7)-x-2/5=9+2x/5
4x+14-x-2=9+2x
4x-x-2x=-14+2+9
x=-3

d)-2(3x+10)-x+8/4=3(x+5)/4
-6x+20-4(-x+8/4)=3x+15
-6x+20-4x+32=3x+15
6x-4x+3x=20-32-15
6x=3/6
x=½
f)(6-x)(x+2)+(x+3)(x-4)=2x+5
6²-x²+x²-3²=2x+5
36-x²-9=2+5
36-x²-9=7
x=36+9-7
x=38

g)(x-5)(x+2)-(3-x)(2-x)=x-12
x²-5²-3²-2²=x-12
x²-32-9-4=x-12
x²-19=x-12
x=19-12
x=7

h)(2x-5)(x+1)-2=(1-x)(8-2x)+2x
2x²-5²-2=1²-2²+2x
4x-32-2=1-4+2x
4x-30=-3+2x
4x-2x=30-3
2x=27/2
x=13½